1998
DOI: 10.1046/j.1365-2842.1998.00247.x
|View full text |Cite
|
Sign up to set email alerts
|

Component release from light‐activated glass ionomer and compomer cements

Abstract: The purpose of this study was to identify and quantify any component released from seven commercially available light-cured or resin-modified glass ionomer and compomer cements. Twenty-one separate cylindrical stainless steel moulds 6 mm in diameter and 1.0 mm deep were filled with one of seven glass ionomer or compomer cements, light activated and then immediately immersed in separate containers of distilled water. Water samples were retrieved over a time period of up to 30 days and retained for analysis. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 33 publications
3
37
0
6
Order By: Relevance
“…The cement was then introduced into a mold to prepare standardized round shaped specimens of 10.0 mm diameter and 2.0 mm height. that substantial amounts of HEMA were released from various commercially available RMGIC into the liquid medium, when studied using liquid chromatography [34,35]. The current study also found that the density of cells increased with decreasing concentration of all the material extracts.…”
Section: Preparation Of the Test Materials And Their Extractssupporting
confidence: 61%
“…The cement was then introduced into a mold to prepare standardized round shaped specimens of 10.0 mm diameter and 2.0 mm height. that substantial amounts of HEMA were released from various commercially available RMGIC into the liquid medium, when studied using liquid chromatography [34,35]. The current study also found that the density of cells increased with decreasing concentration of all the material extracts.…”
Section: Preparation Of the Test Materials And Their Extractssupporting
confidence: 61%
“…This is in agreement with our previous study 7 and with other reports. 13,14 We further demon- strated that all the biomaterials except Z100 MP induced a dose-dependent cellular GSH depletion. This GSH depletion appears to be involved in the cytotoxicity process, as the cytotoxicity effect can be prevented by cell treatment with NAC and, to a lesser extent, with exogenous GSH and cysteine.…”
Section: Discussionmentioning
confidence: 79%
“…1,2,4 It is known that both composite resins and bonding resins release unreacted monomers of methacrylates into the adjacent aqueous phase and that monomers diffuse through dentin to the pulp. 11,12 Hamid et al 13 analyzed the high-performance liquid chromatography water eluates of seven commercially available RM-GIC, and HEMA was detected in each of the eluates. The toxicity of other dentin bonding components, such as Bis-GMA, TEGDMA, and UDMA, also was suggested.…”
Section: Discussionmentioning
confidence: 99%
“…The aqueous eluates of polyacidmodified composite resins were analyzed by gas chromatography/mass spectrometry (GC/MS) and high-performance liquid chromatography (HPLC). Ethylene glycol compounds (comonomers) and the hydrophilic monomer HEMA were the chief constituents identified in these aqueous extracts (Geurtsen et at., 1998b;Hamid et al, 1998). In addition, the following decomposition products of base monomers and several co-initiators were found: N-(2-cyanoethyl)-N-methylaniline (CEMA), 4-N,N-dimethyl amino benzoic acid ethylester (DMABEE), and N,N-dimethyl amino ethyl methacrylate (DMAEMA) (Geurtsen et al, 1998b).…”
Section: (G) Pulp Studies In Animals and Humansmentioning
confidence: 99%